الاشتِغالُ النَّقْدِي بَيْن حدَّيْ المَنهجِ والنَّصِّ عند الجُرجاني والسّكَّاكي - مصطفى, سالمي; سليمان, بن علي (جامعة الوادي - University of Eloued, 2021)
لحقّ أنّ الشاهد البلاغي كان - ولا يزال - ذا تأثير بالغ في مسيرة الدرس البلاغي والنقدي؛ وقد أدَّى هذا إلى ازدياد حركة النّشاط النّقدي، وبخاصّة فيما يتَّصل بنقد الخطاب الشّعري. وإنّ ما يلفت النّظر أنّ الشّاهد البلاغيّ ظلَّ يتردَّد في كتب البلاغة القديمة من عصرٍ إلى عصر، متنقِّلاً من متن إلى تلخيص إلى شرح، ولعلّ السّبب في ذلك كون البلاغة في ذلك الوقت تنحو نحوًا تعليميًّا؛ (قاعدة ومثال لإيضاح القاعدة)، فكانوا يستخدمون البيت الشّعريّ أو الآية القرآنيّة مثالاً أو شاهدًا على القاعدة، وإنْ أدَّى ذلك إلى بَتْرِه عن سياقه، ومن ثَمَّ صار الشّاهد مقرّرا للحكم النّقديّ ودليلا عليه. لذلك رأيت أن أتناول قضيّة الشّاهد البلاغيّ ودوره في تحديد المفاهيم النّقديّة عند العلماء الأوائل تناولاً يهدف في المقام الأول إلى النّظر في كيفيّة قراءة هذه النّصوص الشّواهد وطرق تعامل النّقاد معها قراءةً وتوظيفا وتحليلا، فربما تَقِفُنَا هذه القراءة على طريقة الاشتغال النّقدي عندهم. Abstract: It is true that rhetorical quoting did have and still has a great influence in the development of the study of rhetoric and criticism. This has led to an increase in the activity of the movement of criticism, especially when dealing with poetic discourse analysis . What is striking is that rhetorical quoting did exist in ancient books throughout a number of eras. During these periods of time, it witnessed a set of changes. The initial rough text turned into a summary, and the summary became a set explanations. These changes were due to the fact that the discipline of rhetoric was going towards a new educational path to simplify its teaching either through deduction or induction using poetic and Quranic verses. Quoting in this manner helped in getting judgments and evidences for matters of rhetoric and criticism. Therefore, I decided to deal with this issue of rhetorical quoting and its role in determining concepts of criticism of the early scholars. This study work aims primarily to consider how to read these texts and the ways in which critics deal with them, and how critics implement, read, and analyse them. This work may eneble us to understand how early scientists worked with issues of rhetoric and criticism.
مقال
Keywords: الشّاهد؛ النّقد؛ المنهج؛ النّصّ؛ الجرجانيّ؛ السّكّاكيّ; Criticism; Process; Text; Jerjani; Alskak